mTOR signalling and metabolic regulation of T cell differentiation. - Peter, C; Waldmann, H; Cobbold, S (2010)
T cells constantly monitor energy status and nutrient levels in order to adjust metabolic pathways according to their nutritional status and other environmental stimuli. It is increasingly evident that the regulation of cellular metabolism is tightly coupled to T cell differentiation that ultimately determines the cellular fate. The mammalian target of Rapamycin (mTOR) pathway has emerged as a key player in sensing these nutritional/energetic signals and in addition, acts as a major integrator of growth factor induced signals, so placing mTOR at the core of a signalling network controlling metabolism and cellular fate. The mTOR pathway has been shown to play an important role in determining the differentiation of CD4(+) T cells into inflammatory and regulatory subsets, in the induction of anergy, in the development of CD8(+) memory T cells and the regulation of T cell trafficking.